The Relationship between Share Prices and Company Image on Decisions to Selection of Share Issuers Listed on the Indonesian Stock Exchange - Widjanarko, Wirawan; Faeni, Dewi Puspaningtyas; Pitoyo, Bayu Seno; Handayani, Milda (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to build hypotheses regarding the relationship between variables, which can later be used for further research within the scope of financial management. The writing method in this research is qualitative (library research), where the data comes from previous research. Online media, such as Google Scholar, Publish or Perish, and other academic media, are also used to obtain previous research data. The results of this research are: 1) Share prices are related to the decision to select share issuers listed on the Indonesia Stock Exchange, where share prices not only represent the market value of the company's performance and future but also play an important role in investor decision making; and 2) Company image is related to the decision to select share issuers listed on the Indonesia Stock Exchange, where companies with a good image and reputation are believed to have lower risks so that they can increase investor confidence in their sustainability and long-term success.